Cryptanalysis and improvement of several certificateless digital signature schemes - WANG Hua-qun1; XU Ming-hai2; GUO Xian-jiu1 (Tongxin xuebao)
The security flaws of the certificateless digital signature schemes proposed by Liu-Au-Susilo （2007）,Goranlta-Saxena （2005）,Cao-Paterson-Kou（2006）,Yap-Heng-Goi（2006） and Je Hong Park（2006）were analyzed. It pointed that the schemes couldn’t resist the public key substitution attack. The attack methods were presented. The secu-rity flaws are pointed out,and the attack methods are presented. Then,the flaws that exist in the original digital signatures security proof were enumerated. In order to avoid these flaws,made use of the general certificateless digital signature scheme and the corresponding forking lemmas from Castro-Dahab（2007） to improve the original digital signature schemes. The improved digital signature schemes are provably secure.